2021
DOI: 10.1016/j.jmsacl.2021.11.004
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS lipidomics of renal biopsies for the diagnosis of Fabry disease

Abstract: Highlights Fabry is an X-linked lysosomal storage disease with deficiency in α-galactosidase. This deficiency results in the accumulation of glycosphinogolipids. Diagnosis is often made by analysis of globotriaosylceramide in fluids and tissues. Fabry is often misdiagnosed in female patients due to residual enzyme activity. Lipidomics by LC-HRMS enables identification of new biomarkers in Fabry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…While these data suggest that the aforementioned metabolites may be more sensitive for patient follow-up and monitoring, we would like to emphasize that most untreated patients in our cohort had an attenuated form of the disease. Based on studies performed on other LSDs, it was demonstrated that even after treatment with ERT, residual levels of biomarkers are still present in tissues and biological fluids [ 26 ]. Patients classified as “borderline to mild” typically do not have an important concentration of biomarkers, whereas for patients who are treated, biomarkers levels never truly return to baseline values such as those observed in healthy controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While these data suggest that the aforementioned metabolites may be more sensitive for patient follow-up and monitoring, we would like to emphasize that most untreated patients in our cohort had an attenuated form of the disease. Based on studies performed on other LSDs, it was demonstrated that even after treatment with ERT, residual levels of biomarkers are still present in tissues and biological fluids [ 26 ]. Patients classified as “borderline to mild” typically do not have an important concentration of biomarkers, whereas for patients who are treated, biomarkers levels never truly return to baseline values such as those observed in healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, our research group performed several metabolomic studies in urine on Fabry disease, where glycosphingolipid accumulation is also involved. These studies led to the discovery of novel lyso-Gb 3 analogs with different modifications on the sphingosine moiety [ 25 , 26 ]. Another study highlighted that several lyso-Gb 3 analogs had a significant correlation with specific clinical manifestations of the disease [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rare disorders remain a challenge even to modern medicine, and mounting evidence shows the prominent role of lipidomics in this scenario [12]. In patients with Lipidomics as a Tool in the Diagnosis and Clinical Therapy DOI: http://dx.doi.org/10.5772/intechopen.105857…”
Section: Lipidomics In the Study Of Rare Diseasesmentioning
confidence: 99%
“…Olmsted syndrome caused striking decreases in 15-LOX and dhCer levels [77]. In patients with Fabry disease, the presence of glycosphingolipids, galabiosylceramide, and globotriaosylsphingosine is observed in vascular endothelium, nerves, cardiomyocytes, and renal glomerular podocytes [12]. A dysregulation in lipids involved in both cellular structure and membrane integrity was identified in fragile X syndrome, suggesting that X chromosomal deletion disorders are not limited to alterations in neuronal functions [78].…”
Section: Lipidomics In the Study Of Rare Diseasesmentioning
confidence: 99%
See 1 more Smart Citation